Innovative Use of Administrative Data in Legal Research and Practice - Jay, Matthew A; Byrom, Natalie; Jay, Matthew A; Forell, Suzie (International Journal of Population Data Science, 2020)
Introduction There is widespread recognition of the need to use administrative data from justice, crime, prisons and legal services to improve the evidence base on determinants and outcomes of involvement with justice systems and to improve services. There is great opportunity to use data from justice to improve health and other outcomes for clients and service users but this is a relatively unexplored area and these datasets have been neglected partly due to access concerns. This 90 minute symposium presents research and learning from data initiatives in justice settings and will explore challenges from the perspectives of researchers and the legal profession. Objectives and Approach Talks will cover: Development of legal epidemiology and use of administrative data in this nascent field (Matthew A Jay). Examples from the presenter’s family justice research using linked data will also be presented. The UK Ministry of Justice’s (MoJ’s) Data First programme (Prof Betsy Stanko). Data First aims to unlock the potential of data already created by MoJ, by linking datasets from the justice system and beyond, and enabling accredited researchers to access the data ethically and responsibly. UK court reform and data collection: using data to monitor equality and access to justice in the move to on-line dispute resolution (Dr Natalie Byrom). Health Justice Partnerships (HJPs) in Australia (Prof Suzie Forell). HJPs bring legal help into health settings to address social issues affecting the health of patients. This will be a discussion of HJPs as an opportunity to explore the impact of legal assistance on health and the challenges and opportunities of relevant data generation. Conclusion / Implications Better use of data in justice spheres will be a difficult process requiring cross-disciplinary collaboration. But it is one that promises to bring the study and practice of law into the 21 st Century.